Leaving no one behind: tracking the effectiveness of the Global Partnership for Education Grant in Ghana. Issue 7 (3rd October 2022) - Abubakari, Maliha
ABSTRACT: The Global Partnership for Education (GPE)/Education for All (EFA) seeks to reduce poverty and bridge inequalities through the provision of quality education in developing countries. This paper sets out to accomplish two main objectives: (a) examine the extent to which the Ghana Partnership for Education Grant (GPEG) retained its pro-poor intentions during the course of implementation, and (b) examine if/whether GPEG eschewed resource capture by the political elite. A mixed methodology approach was employed in this study. Findings of the study showed the program was largely implemented in a pro-poor manner and was also devoid of the elite capture of resources.